The Predictors of Spontaneous Coronary Reperfusion in Patients with ST-segment Elevation Myocardial Infarction - Ermawan, Romi; Pintaningrum, Yusra; Sari, Dian Puspita; Indrayana, Yanna; Aprilia, Kartika (Heart Science Journal, 2024)
BACKGROUND: In ST-segment elevation myocardial infarction (STEMI) management, some patients undergo spontaneous coronary reperfusion (SCR) with a better prognosis than those without SCR, but predictors for SCR remain unclear.OBJECTIVE: To investigate several potential predictors of SCR, including smoking status, BMI, DAPT loading time, hemoglobin levels, platelet count, random blood sugar levels, uric acid levels, creatinine clearance, and the Syntax score.METHODS: This case-control study was conducted at the West Nusa Tenggara General Hospital in Indonesia from December 2022 to September 2023. Data collection encompassed various patient demographics and clinical parameters, including name, medical record number, age, gender, smoking status, BMI, DAPT loading time, hemoglobin levels, platelet count, random blood sugar, uric acid, creatinine clearance, the Syntax score, and the occurrence of SCR. Statistical analysis for this study involved multivariate logistic regression analysis.RESULTS: A total of thirty-two patients was included, evenly divided into 16 subjects allocated to the SCR group and 16 to the non-SCR group. The analysis indicated that only BMI demonstrated a statistically significant association with SCR occurrence. However, the study did not yield conclusive evidence regarding the influence of smoking status, DAPT loading time, hemoglobin levels, platelet count, random blood sugar levels, uric acid levels, creatinine clearance, and the Syntax score on the likelihood of SCR.CONCLUSION: A normal BMI is identified as a robust predictor for the incidence of SCR in patients diagnosed with STEMI.